Development of a Website-Based E-Module to Improve Student Learning Outcomes on Starter System Material at SMK Teuku Umar - Ridha Al Rizqi; Bunyamin; Wahyudi; Dwi Widjanarko (JMEL : Journal of Mechanical Engineering Learning, 2026)
This study aimed to develop and examine the feasibility and effectiveness of a website-based starter system e-module for Grade XI students in the Light Vehicle Engineering Department at SMK Teuku Umar. This study employed a research and development approach using the ADDIE model, which consists of Analyze, Design, Development, Implementation, and Evaluation stages. The effectiveness of the product was tested using a one-group pretest–posttest design involving 29 Grade XI TKR 1 students. The instruments used in this study included expert validation sheets, learning outcome tests, and a student response questionnaire. The feasibility test involved two media experts and two subject matter experts. The results showed that the developed e-module was categorized as very feasible, with validation scores of 92.36% from media experts and 91.66% from subject matter experts. The learning outcome test showed that students’ mean score increased from 47 in the pretest to 76 in the posttest. The paired-sample t-test indicated a significant improvement in students’ learning outcomes, with tcount = 18.36, which was higher than ttable = 2.048. The N-Gain score was 0.5582, or 55.82%, indicating a moderate level of effectiveness. Student responses reached 85%, categorized as very positive. Therefore, the website-based starter system e-module is feasible and moderately effective for supporting starter system learning. However, this study was limited to one class and did not involve a control group; therefore, broader trials with comparison groups are recommended.